1997
DOI: 10.1001/archsurg.1997.01430290045007
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Prospective Trial of Deep Venous Thrombosis Prophylaxis in Aortic Surgery

Abstract: The incidence of proximal DVT in patients undergoing elective aortic reconstruction is low compared with patients undergoing other major intraabdominal general surgical procedures. The use of aggressive DVT prophylaxis did not reduce the risk of postoperative proximal DVT in this study. The selective use of DVT prophylaxis in patients undergoing elective aortic surgery should be based on associated concomitant or evolving risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
0
31
1
Order By: Relevance
“…Obesity and perioperative stasis and hypercoagulability place most bariatric surgery patients at high risk for 109,111,115 the pooled weighted risk of major bleeding in the control (no prophylaxis) groups was 0.3% (95% CI, 0.2%-2.4%). However, an observational study reported that the incidence of life-threatening hemorrhage among 973 patients undergoing complex major vascular procedures was 1.8%, with most episodes of bleeding occurring intraoperatively and only 0.4% of patients experiencing severe bleeding postoperatively.…”
Section: Baseline Risk Risk Factors and Risk Stratifi Cation For Vtmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and perioperative stasis and hypercoagulability place most bariatric surgery patients at high risk for 109,111,115 the pooled weighted risk of major bleeding in the control (no prophylaxis) groups was 0.3% (95% CI, 0.2%-2.4%). However, an observational study reported that the incidence of life-threatening hemorrhage among 973 patients undergoing complex major vascular procedures was 1.8%, with most episodes of bleeding occurring intraoperatively and only 0.4% of patients experiencing severe bleeding postoperatively.…”
Section: Baseline Risk Risk Factors and Risk Stratifi Cation For Vtmentioning
confidence: 99%
“…[109][110][111][112][113][114][115][116] Most enrolled patients undergoing diverse vascular procedures, but two studied patients undergoing aortic surgery, 109,115 and one enrolled patients undergoing lower-extremity amputation. 116 Three studies compared LDUH (with or without IPC) to no prophylaxis, one compared aspirin to no prophylaxis, and three compared LDUH to LMWH.…”
Section: Target Population: Vascular Surgerymentioning
confidence: 99%
“…22 In the absence of prophylaxis, the rate of DVT is Ϸ21% when routine contrast venography is obtained [23][24][25] and 15% when routine postoperative ultrasonography is performed. 22,26 Patients undergoing major vascular procedures who have additional thromboembolic risk factors should receive antithrombotic prophylaxis with LDUH or LMWH. Although the optimal time to start prophylaxis with antithrombotic agents in patients undergoing vascular surgery remains unclear, some practitioners prefer to administer the first dose after surgery.…”
Section: Vascular Surgerymentioning
confidence: 99%
“…The lowest frequency of thrombosis was observed by Killewich, at 2% in both study groups with and without pharmacological antithrombotic prophylaxis [18]. However, in his research he totally ignored the diagnostics of crural veins, which, according to our observations, constituted the most frequent location of thrombotic lesions.…”
Section: Discussionmentioning
confidence: 48%
“…In other studies the above ratio moved gradually in the proximal direction, amounting to, respectively, for the distal and proximal section, 78% and 22% [21], 67% and 33% [22], and 52% and 48% [29]. Fletcher and Batiste observed proximal thrombosis in as many as 80% of patients with TC [20], whereas Killewich detected the presence of thrombus only in proximal veins [18]. However, according to the examination report, during a DUS scan he did not assess the lower leg veins.…”
Section: Discussionmentioning
confidence: 91%